ANALISIS PERILAKU MASYARAKAT YANG BERMUKIM DI BANTARAN SUNGAI ACAI KOTA JAYAPURA - Yenni Pigome; Mujiati Mujiati; Harmonis Rante (Jurnal ELIPS (Ekonomi, Lingkungan, Infrastruktur, Pengembangan Wilayah, dan Sosial Budaya), 2021)
The riverbank area is a waterfront area that has several advantages, especially those related to more strategic functions and accessibility. The geographical condition of the State of Indonesia, especially Papua Province, which has many rivers as a life orientation, makes the riverbanks a place to live and get a livelihood. This study aims to determine or identify the factors that influence environmental pollution of the Acai River, analyze community behavior towards environmental conditions, what efforts can be made in environmental management and what are the activities and behavior of the people living on the banks of the Acai River. The results showed that the factors that influence the pollution are the lack of garbage collection basins, disposal of activity waste to the community into the river. Then the behavior of the community still does not pay attention to the environment and does not care about the condition of the environment around them, especially regarding the Kali Acai River. Recommendations of this study are intense socialization to raise awareness to the community, and intense cross-stakeholder care involving elements of the government, NGOs and local communities to produce integrated environmental management.